ANALISIS PERAN STAKEHOLDERS DALAM PENGELOLAAN HUTAN MANGROVE TAPAK DI KELURAHAN TUGUREJO, KOTA SEMARANG - Aulia Sofyan, Hairunisa; Zarkasyi Rahman, Amni; Hanani, Retna (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2024)
This research aims to identify and analyze the role of stakeholders in managing the Tapak Mangrove Forest in Tugurejo Village, Semarang City. The method used in the research is descriptive qualitative. The research results show that Central Java Provincial Environment and Forestry Service as government elements who plays the role as a policy creator and facilitator. The Semarang City Environmental Service and the Semarang City Fisheries Service from the government act as facilitators. Tugurejo Subdistrict is a stakeholder from the government element who acts as a coordinator. CV Akar Energi Mandiri is a private stakeholder with a role as a facilitator. Community services of HMIK FPIK Undip is a stakeholder from academic elements who plays the role of facilitator and accelerator. Furthermore, the Prenjak Group and Pokdarwis Bina Tapak Lestari from community elements who plays as coordinators, facilitators and implementers. Last, Community of Tapak from society elements who plays the role as facilitator. Therefore, there needs to be efforts from all stakeholders involved to carry out management according to their respective roles and duties.